Book Review: Undoing the Demons - Zhang, Heidi (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2018)
Book review of Undoing the Demons: Neoliberalism’s Stealth Revolution. By Wendy Brown. New York: Zone Books, 2015. 292 pages. ISBN: 978-1-935408-54-3